Sealing structure, flat plate type RSOC electric pile and preparation method of flat plate type RSOC electric pile
By using the sealing structure of the Fe-16Cr alloy sealing body and SiO2-TiO2-Na2O-K2O-Al2O3 amorphous glass system in a flat plate RSOC stack, the stability problem caused by sealing material failure is solved and low gas leakage is achieved The rate and high-temperature structural support ensure the long-term and stable operation of the stack.
Patent Information
- Application Number
- CN202411258214.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-09
AI Technical Summary
In the prior art, flat-panel RSOC stacks cannot operate stably due to failure of sealing materials, and it is difficult to achieve dual functions of airtightness and structural support at the same time.
The amorphous glass system consisting of a Fe-16Cr alloy sealing body with multiple pores and SiO2-TiO2-Na2O-K2O-Al2O3 is combined. The rigid material layer completely covers the upper and lower sides of the sealing body, and fills the pores by pumping and suction. , a sealing structure is formed by combining heating and pressurization treatment.
It achieves low gas leakage rate and high-temperature structural support, reduces the probability of sealing high-temperature failure, and ensures the long-term and stable operation of the flat-panel RSOC stack.
Smart Images

Figure CN119252965A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of reversible solid oxide batteries, and in particular to a sealing structure, a flat-plate RSOC battery stack and a preparation method thereof. Background Art
[0002] RSOC (Reversible Solid Oxide Cell) is an electrochemical conversion device that can not only convert chemical energy into electrical energy in fuel cell mode, but also convert electrical energy into chemical energy in electrolytic cell mode. The successful application of this technology is of great significance in alleviating the energy crisis, protecting the living environment and ensuring my country's energy security. The battery stack is the core working unit of the RSOC system and is composed of RSOC single cells connected in series. Among them, the flat-plate RSOC has great commercial potential due to its advantages of high power density and low preparation cost. High-temperature sealing is the main bottleneck restricting the development of battery stack technology. The battery stack is composed of repeated units (single cell / sealing material / metal connector).
[0003] Sealing materials are an important component of the fuel cell stack. They are mainly used to isolate fuel gas and oxidizing gas to avoid performance degradation or even explosion due to gas mixing, and to achieve insulation of different components. However, the existing various high-temperature sealing materials are difficult to meet the requirements of performance and structure at the same time.
[0004] Therefore, there is an urgent need in the art for a sealing structure that can simultaneously achieve the dual functions of airtightness and structural support, so as to ensure that the flat-plate RSOC stack can have a stable interface seal and maintain a stable structure during operation. Summary of the invention
[0005] The purpose of the present invention is to provide a sealing structure, a flat-plate RSOC stack and a preparation method thereof, so as to solve the technical problem in the prior art that the flat-plate RSOC stack cannot operate stably due to failure of the sealing material.
[0006] In order to solve the above technical problems, the present invention first provides a sealing structure, comprising a sealing body having a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body, and each pore is completely filled with the rigid material layer; The sealing body is made of Fe-16Cr alloy, and the rigid material layer includes SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 Amorphous glass system.
[0007] Preferably, in the sealing body: the porosity is 60% to 80%, the pore diameter is 0.1 to 1 mm, the line diameter is 0.05 to 0.1 mm, and the thickness is 0.3 to 0.5 mm.
[0008] Preferably, the components of the amorphous glass system are: 60-65wt% SiO 2 、15-20wt%TiO 2 、10~15wt%Na 2 O, 5~10wt%K 2 O and Al 2 O 3 , Al 2 O 3 The mass fraction is greater than 0 and less than or equal to 5wt%.
[0009] Preferably, the glass softening temperature of the amorphous glass system is 600-700° C., and the median particle size of the amorphous glass powder in the amorphous glass system is 3-20 μm.
[0010] Preferably, the thermal expansion coefficients of the sealing body and the amorphous glass system are (10~12)×10 -6 / K.
[0011] Correspondingly, the present invention also provides a flat-plate RSOC stack, which is formed by stacking a plurality of repeating units, each repeating unit comprising a metal connector stacked in sequence from bottom to top, a sealing structure as described above, and a single cell.
[0012] Accordingly, the present invention further provides a method for preparing the above flat-plate RSOC stack, the method comprising: S10, mechanically mixing the amorphous glass powder with the organic solvent to obtain an amorphous glass slurry, wherein the amorphous glass powder is SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The amorphous glass system composed of S20, using a pumping method to completely cover the upper and lower sides of the sealing body with amorphous glass slurry and fill the plurality of pores of the sealing body to obtain a preliminary sealing material; S30, stacking the metal connector, the prepared sealing material and the single battery in sequence to form a prepared repeating unit, and assembling a plurality of the prepared repeating units to form a prepared battery stack; S40, heating and pressurizing the prepared fuel cell stack to obtain a fuel cell stack with a sealed structure.
[0013] Preferably, in step S10: the content of amorphous glass powder in the amorphous glass slurry is 50-70wt%.
[0014] Preferably, in step S10: the organic solvent is terpineol to which ethyl cellulose is added, and the content of ethyl cellulose in the organic solvent is 3-4 wt %.
[0015] Preferably, during the heating and pressurizing process of step S40: the heating temperature is 800-850° C., the heating rate is 2-10° C. / min, the pressurizing pressure is 0.05-0.2 MPa, and the time is 1-3 h.
[0016] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention provides a sealing structure, a flat RSOC stack and a preparation method thereof, wherein the sealing structure comprises a sealing body having a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body, and each pore is completely filled with the rigid material layer, wherein the material of the sealing body is Fe-16Cr alloy, and the rigid material layer comprises SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The sealing structure provided by the present invention combines the foam metal Fe-16Cr alloy with high-temperature structural support and the amorphous glass system with excellent sealing performance, which can simultaneously achieve the low gas leakage rate and high-temperature structural support of the sealing structure. The amorphous glass system can provide effective interface sealing through sufficient deformation, thereby reducing the probability of high-temperature failure of the seal. It is particularly suitable for the interlayer sealing of the flat-plate RSOC stack, thereby ensuring the long-term stable operation of the flat-plate RSOC stack. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic diagram of the structure of the sealing structure provided by an embodiment of the present invention at 20°C and 750°C; Figure 2 is a structural schematic diagram of a sealing body in a sealing structure provided by an embodiment of the present invention; Figure 3 is a flow chart of a method for preparing a flat-plate RSOC stack provided by an embodiment of the present invention; Figure 4 is a thermal expansion curve of the rigid material layer in the sealing structure provided in Example 1 of the present invention; Figure 5 It is a curve showing the change of the wetting angle of H-5 glass on Fe-16Cr alloy and a schematic diagram of high temperature deformation in the sealing structure provided in Example 1 of the present invention; Figure 6is the gas leakage rate of H-5 glass in the sealing structure provided in Example 1 of the present invention in 5 cooling and heating cycles; In the figure, 10 is a metal connector; 20 is a sealing structure; 21 is a sealing body; and 30 is a single cell. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] At present, the sealing materials used for flat-type RSOC stacks can be divided into compression sealing materials, flexible sealing materials and rigid material layers. Compression sealing materials represented by ceramic-based materials require a large external loading pressure to achieve sealing, and generally have the problem of high leakage rate; flexible sealing materials based on precious metals have high preparation costs and complex processing technology. The rigid material layer can achieve effective interface sealing with adjacent components through chemical bonding and adhesion, and is low-cost and easy to manufacture.
[0021] Glass is a common rigid material layer, which can be divided into microcrystalline glass and amorphous glass according to its crystallization trend. Microcrystalline glass has many advantages such as low air leakage rate, and the crystal phase in the glass matrix can serve as a skeleton to maintain the supporting structure of the sealing material. However, it will undergo uncontrollable crystallization during the heat treatment process. The precipitated crystal phase may change the thermal properties of the sealing material such as the thermal expansion coefficient, affecting the stability of itself and its combination with adjacent components.
[0022] Therefore, amorphous glass with excellent sealing performance and stable chemical properties has become a research focus. It can not only provide effective interface sealing through sufficient deformation, but also has good chemical compatibility with adjacent components, which will lay the foundation for achieving long-term stable performance of the battery stack. However, the large deformation of amorphous glass during the sealing process can easily cause structural instability of the battery stack, which has become a new problem to be solved. Various existing high-temperature sealing materials are difficult to meet the requirements of functional characteristics and structural support at the same time. Therefore, this field urgently needs to develop new sealing materials and structures to achieve low leakage rate and high-temperature structural support of sealing materials at the same time to ensure long-term stable operation of the battery stack.
[0023] In view of this, the present invention first provides a sealing structure 20 suitable for the interlayer of a flat-plate RSOC stack component, which combines a foam metal Fe-16Cr alloy with a high-temperature structural support function with an amorphous glass system with excellent sealing performance, while achieving a low gas leakage rate and high-temperature structural support of the sealing structure 20, and deformation under a specific pressure, thereby reducing the probability of high-temperature failure of the seal, and is particularly suitable for the interlayer sealing of a flat-plate reversible solid oxide battery stack.
[0024] See also Figure 1 , Figure 1 A schematic diagram of the structure of the sealing structure 20 provided in an embodiment of the present invention at 20°C and 750°C; wherein the sealing structure 20 comprises a sealing body 21 having a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body 21, and each pore is completely filled with the rigid material layer; The sealing body 21 is made of Fe-16Cr alloy, and the rigid material layer includes SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The amorphous glass system (H-5 glass) is composed of the following: the material of the sealing body 21 is Fe-16Cr alloy, which can support the sealing structure 20; the amorphous glass system is selected for the rigid material layer, which can not only provide effective interface sealing through sufficient deformation, but also has good chemical compatibility with adjacent components, which will lay the foundation for achieving long-term stable performance of the fuel cell stack.
[0025] Specifically, both the upper and lower sides of the sealing body 21 are covered with a complete rigid material layer, thereby ensuring that the high-temperature insulation performance of the sealing structure 20 meets the requirements.
[0026] For details, please continue to see Figure 1 When the sealing structure 20 is at 20°C, the rigid material layer does not deform; when the sealing structure 20 is at 750°C, the rigid material layer begins to deform.
[0027] See also Figure 2 , Figure 2 : is a schematic diagram of the structure of the sealing body 21 in the sealing structure 20 provided in an embodiment of the present invention; wherein, in the sealing body 21: the porosity is 60% to 80%, the pore size is 0.1 to 1 mm, the wire diameter is 0.05 to 0.1 mm, and the thickness is 0.3 to 0.5 mm; wherein, a higher porosity is conducive to doping a sufficient amount of amorphous glass system, and a smaller pore size and wire diameter may help improve the accuracy and stability of the seal. The selection of the appropriate thickness of the sealing body 21 may be a comprehensive result of taking into account factors such as material cost and structural strength while ensuring the sealing effect.
[0028] Specifically, the rigid material layer is a high-temperature thermally stable amorphous glass, and the components of the amorphous glass system are: 60~65wt% SiO 2 、15-20wt%TiO 2 、10~15wt%Na 2 O, 5~10wt%K 2 O and Al 2 O 3 , Al 2 O 3 The mass fraction of SiO is greater than 0 and less than or equal to 5wt%; 2 Can provide good chemical stability and mechanical strength for amorphous glass system; TiO 2 It helps to improve some physical properties of amorphous glass, such as refractive index; Na 2 O can reduce the melting temperature and viscosity of amorphous glass to a certain extent, which is helpful for processing; K 2 O and Na 2 O is similar to Al, and can also regulate the properties of amorphous glass; 2 O 3 The content is greater than 0 and less than or equal to 5wt%. Although the content is small, it may affect the structure and properties of amorphous glass, such as improving the chemical corrosion resistance of non-glass.
[0029] Specifically, the glass softening temperature of the amorphous glass system is 600-700° C., and the median particle size of the amorphous glass powder in the amorphous glass system is 3-20 μm.
[0030] Specifically, the thermal expansion coefficients of the sealing body 21 and the amorphous glass system are (10~12)×10 -6 / K; where the thermal expansion coefficient indicates the degree to which a material expands or contracts in size when the temperature changes. When the thermal expansion coefficients of the sealing body 21 and the amorphous glass system match, they can expand and contract at similar rates in a temperature-changing environment, thereby reducing internal stress and possible damage caused by differences in thermal expansion and contraction.
[0031] Accordingly, please continue to refer to Figure 1 The present invention also provides a flat-plate RSOC stack, which is formed by stacking a plurality of repeating units, each repeating unit comprising a metal connector 10, a sealing structure 20 as described above, and a single cell 30 stacked in sequence from bottom to top.
[0032] See also Figures 1 to 3 , Figure 3 : is a flow chart of a method for preparing a flat-plate RSOC stack provided by an embodiment of the present invention; wherein the above-mentioned preparation method specifically includes: S10, mechanically mixing the amorphous glass powder with the organic solvent to obtain an amorphous glass slurry, wherein the amorphous glass powder is SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 Amorphous glass system.
[0033] Specifically, step S10 also includes: First, an amorphous glass powder is provided. The amorphous glass powder is H-5 glass, which is SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The amorphous glass system composed of Secondly, the amorphous glass powder and the organic solvent are mechanically mixed in a high-energy ball mill at a rotation speed of 300-400 r / min to obtain an amorphous glass slurry.
[0034] Specifically, the content of amorphous glass powder in the amorphous glass slurry is 50~70wt%; the organic solvent is pineol with ethyl cellulose added, and the content of ethyl cellulose in the organic solvent is 3~4wt%; the appropriate pineol content can ensure that the amorphous glass slurry has good filling and stability during the molding process; the addition of ethyl cellulose helps to increase the viscosity and stability of the organic solvent, thereby improving the overall performance of the amorphous glass slurry.
[0035] S20 , using a pumping method to completely cover the upper and lower sides of the sealing body 21 with amorphous glass slurry and fill the plurality of pores of the sealing body 21 , thereby obtaining a preliminary sealing material.
[0036] Specifically, step S20 also includes: The amorphous glass slurry is completely covered on the upper and lower sides of the sealing body 21 by a pumping method and filled into multiple pores of the sealing body 21 to obtain a prepared sealing material; wherein, the upper and lower sides of the sealing body 21 are covered with a complete rigid material layer, thereby ensuring that the high-temperature insulation of the sealing structure 20 meets the requirements.
[0037] S30 , stacking the metal interconnect 10 , the preliminary sealing material and the single cells 30 in sequence to form a preliminary repeating unit, and assembling a plurality of preliminary repeating units to form a preliminary battery stack.
[0038] Specifically, step S30 also includes: The metal interconnector 10 , the preliminary sealing material and the single cells 30 are stacked in sequence to form a preliminary repeating unit, and a plurality of preliminary repeating units are assembled by stacking to form a preliminary battery stack.
[0039] S40 , heating and pressurizing the prepared fuel cell stack to obtain a fuel cell stack having a sealing structure 20 .
[0040] Specifically, step S40 also includes: The prepared battery stack is heated and pressurized at the same time, and the amorphous glass slurry in the prepared sealing material is deformed by heat to provide sufficient interface sealing, and the leakage channel can be blocked by the viscous flow of the amorphous glass system during operation to achieve self-healing; at the same time, the reduction in thickness of the amorphous glass system during the sealing process can reduce the accumulated thermal stress at the interface (the interface where the prepared sealing material contacts the metal connector 10 or the single cell 30), avoid cracks at the interface that lead to sealing failure, thereby significantly improving the adhesion strength of the interface, and finally obtaining a battery stack with a sealing structure 20.
[0041] Furthermore, during the heating and pressurizing process: the heating temperature is 800-850°C, the heating rate is 2-10°C / min, the pressurizing pressure is 0.05-0.2MPa, and the time is 1-3h.
[0042] Among them, a higher heating temperature can ensure that the temperature of the amorphous glass slurry is greater than the softening temperature of the glass, and the amorphous glass slurry is easy to deform and flow; a lower heating rate can slowly volatilize organic matter and reduce the generation of leakage holes in the sealing structure 20.
[0043] Furthermore, the pressurizing direction is perpendicular to the upper and lower sides of the sealing body 21 , and a relatively large loading pressure (0.05-0.2 MPa) can ensure that the interfaces where the sealing structure 20 contacts the metal connector 10 and the single cell 30 are effectively connected.
[0044] Specifically, during the heating and pressurizing process, the organic matter in the amorphous glass slurry burns and volatilizes, the glass softens, flows, sinters, and forms an interface seal with adjacent components. The foam metal Fe-16Cr alloy undergoes a certain degree of deformation due to the compressive state and the high-temperature softening of the H-5 glass, which will provide high-temperature structural support for the seal.
[0045] Specifically, the sealing mechanism process of the above-mentioned flat-plate RSOC stack is as follows: when the prepared sealing material is under high temperature and pressure, the foam metal Fe-16Cr alloy exhibits elastic properties to a certain extent. When the loading pressure is 0.05~0.2MPa, the deformation of the Fe-16Cr alloy can meet the interface connection requirements between the single cell 30 and the metal connector 10, thereby effectively reducing the contact resistance of the interface. H-5 glass is filled in the gaps inside the Fe-16Cr alloy and on the upper and lower surfaces in a high-temperature molten state, and can deform with the Fe-16Cr alloy at an operating temperature of 650°C to 800°C. In view of the fact that the thermal expansion coefficient of H5 glass is similar to that of Fe-16Cr alloy, the two will not produce thermal stress concentration due to temperature changes.
[0046] The technical solution of the present application is now described in conjunction with specific embodiments.
[0047] Embodiment 1: Embodiment 1 of the present invention firstly proposes a sealing structure 20, which includes a sealing body 21 having a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body 21, and each pore is completely filled with the rigid material layer; The sealing body 21 is made of Fe-16Cr alloy, and the rigid material layer includes SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 Amorphous glass system (H-5 glass) composed of.
[0048] Specifically, the porosity of the Fe-16Cr alloy is 80%, the pore diameter is 6 mm, the wire diameter is 0.2 mm, and the thickness is 0.35 mm.
[0049] Specifically, the SiO in the H-5 glass of the rigid material layer 2 、TiO 2 、Na2 O.K 2 O and Al 2 O 3 The mass fractions of H-5 glass powder are 64wt%, 18wt%, 10wt%, 7wt% and 1wt% respectively. The softening temperature of H-5 glass is 610℃. The median particle size of H-5 amorphous glass powder is 15μm. The thermal expansion coefficient of H-5 glass is 11.0×10 -6 / K.
[0050] Correspondingly, Embodiment 1 of the present invention further provides a planar RSOC stack, which is formed by stacking a plurality of repeating units, each repeating unit comprising a metal connector 10, a sealing structure 20 as described above, and a single cell 30 stacked in sequence from bottom to top.
[0051] Accordingly, Embodiment 1 of the present invention further provides a method for preparing a planar RSOC stack, the method comprising: First, H-5 amorphous glass powder and an organic solvent are mechanically mixed in a high-energy ball mill at a speed of 350 r / min to obtain an amorphous glass slurry; wherein the content of H-5 amorphous glass powder in the amorphous glass slurry is 60wt%; the organic solvent is pine alcohol with ethyl cellulose added, and the content of ethyl cellulose in the organic solvent is 3wt%.
[0052] Next, the amorphous glass slurry is completely covered on the upper and lower sides of the sealing body 21 and filled into the multiple pores of the sealing body 21 by a pumping method to obtain a preliminary sealing material.
[0053] Next, the metal interconnector 10 , the preliminary sealing material and the single cells 30 are stacked in sequence to form a preliminary repeating unit, and a plurality of preliminary repeating units are assembled by stacking to form a preliminary battery stack.
[0054] Finally, the prepared fuel cell stack is heated and pressurized to obtain a fuel cell stack having a sealing structure 20; wherein, during the heating and pressurization process: the heating temperature is 850°C, the heating rate is 2°C / min, the pressurization pressure is 0.1MPa, and the time is 2h.
[0055] Furthermore, the performance test was performed on the battery stack with the sealing structure 20 prepared in Example 1: See also Figure 4 , Figure 4 is the thermal expansion curve of the rigid material layer in the sealing structure 20 provided in Example 1 of the present invention; wherein Figure 4 It can be seen that the glass transition temperature Tg of the H-5 glass provided in Example 1 of the present invention is 566°C, the glass softening temperature Ts of the H-5 glass is 593°C, and the thermal expansion coefficient CTE of the H-5 glass is 11.04×10-6 / K.
[0056] See also Figure 5 , Figure 5 1 is a curve showing the change of the wetting angle of H-5 glass on Fe-16Cr alloy and the high temperature deformation diagram in the sealing structure 20 provided in Example 1 of the present invention; specifically, the wetting change process of H-5 glass on the substrate Fe-16Cr alloy with temperature is tested, and the test results are shown in FIG. Figure 5 As shown: H-5 glass powder was pressed under a loading pressure of 12 MPa for 2 minutes to obtain a glass cylinder with a diameter of 10 mm and a height of 5 mm; then the glass cylinder was placed on a 50×50×1 mm sheet metal substrate and placed in a tubular furnace for heating treatment, and the heating rate from 700 to 950°C was 5°C / min.
[0057] Please continue reading Figure 5 Schematic diagram of high temperature deformation in Figure 5 The lower left figure shows that the H-5 glass powder exhibits good wettability on the metal substrate of Fe-16Cr alloy, and the molten glass at 900°C can effectively wet the metal connector 10 to form a good bonding interface.
[0058] Furthermore, the air tightness of the sealing structure 20 is tested as follows: Specifically, the principle of the airtightness test of the above-mentioned sealing structure 20 is: disassemble the flat-plate RSOC stack to obtain the sealing structure 20, apply a certain loading pressure of 0.15MPa to the sealing structure 20 and the Fe-16Cr alloy fixture, and the sealing structure 20, the Fe-16Cr alloy fixture, the leakage gas test flowmeter and the incoming gas flowmeter together constitute a closed space; then, heat the temperature of the Fe-16Cr alloy fixture and the sealing structure 20 to 750°C, and under the ventilation pressure of 13.8~20.7kPa, once gas leakage occurs in the sealing structure 20, the leakage gas test flowmeter will display the leakage amount, and the gas leakage rate at high temperature can be measured.
[0059] Specifically, the preparation process of the above-mentioned sealing structure 20 is as follows: cut the prepared cast tape into a circular frame with an outer frame of 70mm×70mm and an inner frame of 50mm×50mm; apply adhesive on the circular frame and place it in a Fe-16Cr alloy fixture to ensure that the sealing structure 20 is tightly combined with the Fe-16Cr alloy fixture; subsequently, perform an airtightness test on the sealing structure 20 under different ventilation pressures, and perform multiple tests on the same sealing structure 20 to ensure the accuracy and reliability of the data.
[0060] See also Figure 6 , Figure 6is the gas leakage rate of H-5 glass in the sealing structure 20 provided in Example 1 of the present invention in 5 cooling and heating cycles. Figure 6 It can be seen that the gas leakage rate of H-5 glass is stably lower than 0.004 sccm / cm, and the gas leakage rate shows a slightly decreasing trend with the increase of the number of hot and cold cycles, demonstrating good sealing performance.
[0061] Compared with the prior art, the present invention has the following advantages: First, the SiO2 in the sealing structure 20 directly contacts the adjacent components of the stack. 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The amorphous glass system can maintain an amorphous structure at the operating temperature of the battery stack and has excellent long-term high-temperature stability. The contact angle between the glass of the system and the metal connector 10 can be less than 90°, thereby ensuring good interface sealing during the sealing process and achieving a low gas leakage rate of the sealing structure 20.
[0062] Secondly, during the heating and pressurizing process, the organic matter in the amorphous glass slurry burns and volatilizes, the glass softens, flows, sinters, and forms an interface seal with adjacent components. The foam metal Fe-16Cr alloy undergoes a certain degree of deformation due to the pressure state and the high-temperature softening of the H-5 glass, which will provide high-temperature structural support for the seal.
[0063] In summary, different from the prior art, the present invention provides a sealing structure 20, a flat RSOC stack and a preparation method thereof, wherein the sealing structure 20 comprises a sealing body 21 having a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body 21, and each pore is completely filled with the rigid material layer, wherein the material of the sealing body 21 is Fe-16Cr alloy, and the rigid material layer comprises SiO 2 -TiO 2 -Na 2 OK 2 O-Al 2 O 3 The sealing structure 20 provided by the present invention combines the foam metal Fe-16Cr alloy with high-temperature structural support and the amorphous glass system with excellent sealing performance, which can simultaneously achieve the low gas leakage rate and high-temperature structural support of the sealing structure 20. The amorphous glass system can provide effective interface sealing through sufficient deformation, thereby reducing the probability of high-temperature failure of the seal. It is particularly suitable for the interlayer sealing of the flat-plate RSOC stack, thereby ensuring the long-term stable operation of the flat-plate RSOC stack.
[0064] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0065] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A sealing structure, characterized in that: It comprises a sealing body with a plurality of pores and a rigid material layer, wherein the rigid material layer completely covers the upper and lower sides of the sealing body, and each of the pores is completely filled with the rigid material layer; The sealing body is made of Fe-16Cr alloy, and the rigid material layer includes an amorphous glass system composed of SiO2-TiO2-Na2O-K2O-Al2O3.
2. The sealing structure according to claim 1, characterized in that: In the sealing body, the porosity is 60% to 80%, the pore diameter is 0.1 to 1 mm, the wire diameter is 0.05 to 0.1 mm, and the thickness is 0.3 to 0.5 mm.
3. The sealing structure according to claim 1, characterized in that: The components of the amorphous glass system are: 60-65wt% SiO2, 15-20wt% TiO2, 10-15wt% Na2O, 5-10wt% K2O and Al2O3, and the mass fraction of Al2O3 is greater than 0 and less than or equal to 5wt%.
4. The sealing structure according to claim 1, characterized in that: The glass softening temperature of the amorphous glass system is 600-700° C., and the median particle size of the amorphous glass powder in the amorphous glass system is 3-20 μm.
5. The sealing structure according to claim 1, characterized in that: The thermal expansion coefficients of the sealing body and the amorphous glass system are both (10~12)×10 -6 / K.
6. A flat-plate RSOC stack, characterized in that: The planar RSOC stack is formed by stacking a plurality of repeating units, each of which comprises a metal connector, a sealing structure as claimed in any one of claims 1 to 5, and a single cell, which are stacked in sequence from bottom to top.
7. A method for preparing a flat-plate RSOC stack as claimed in claim 6, characterized in that: The method comprises: S10, mechanically mixing an amorphous glass powder with an organic solvent to obtain an amorphous glass slurry, wherein the amorphous glass powder is an amorphous glass system composed of SiO2-TiO2-Na2O-K2O-Al2O3; S20, using a pumping method to completely cover the upper and lower sides of the sealing body with the amorphous glass slurry and fill the plurality of pores of the sealing body to obtain a preliminary sealing material; S30, stacking the metal interconnect, the preliminary sealing material and the single battery in sequence to form a preliminary repeating unit, and assembling a plurality of the preliminary repeating units to form a preliminary battery stack; S40, heating and pressurizing the prepared fuel cell stack to obtain the fuel cell stack having the sealing structure.
8. The method for preparing a flat-plate RSOC stack according to claim 7, characterized in that: In the step S10: the content of the amorphous glass powder in the amorphous glass slurry is 50-70wt%.
9. The method for preparing a flat-plate RSOC stack according to claim 7, characterized in that: In the step S10, the organic solvent is terpineol added with ethyl cellulose, and the content of ethyl cellulose in the organic solvent is 3-4 wt %.
10. The method for preparing a flat-plate RSOC stack according to claim 7, characterized in that: During the heating and pressurizing treatment in step S40, the heating temperature is 800-850°C, the heating rate is 2-10°C / min, the pressurizing pressure is 0.05-0.2MPa, and the time is 1-3h.
Citation Information
Patent Citations
Cell stack device of flat solid oxide fuel cell
CN101777662A
Exhaust gas heating device, having a metal foam heating element
CN112832887A
Gradient function sealing structure between flat plate type reversible solid oxide battery stack assembly layers and preparation method thereof
CN117423849A
Barrier layer useful as sealing member in fuel cell, comprises metal comprising barium oxide and strontium oxide-free semi-crystalline sealing glass, which contains silicon dioxide, boron oxide, aluminum oxide and / or magnesium oxide
DE102011011107A1
Porous structure, and solid oxide fuel cell and fuel cell stack using the same
JP2008159428A
